2001
DOI: 10.2320/jinstmet1952.65.6_495
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Crystallographic Structure of Electrodeposited Ni-P AlloyFilm and Its Thermal Equilibrium Diagram

Abstract: The electrodeposited Ni-P alloy films were obtained from Watts baths containing H 3 PO 3 . The crystallographic structure and morphology of electrodeposited Ni-P films were studied by using XRD, HRTEM, SEM and heat-treatment technique. The crystallographic structures of electrodeposited Ni-P alloy films was also compared with the Ni-P thermal equilibrium diagram.The X-ray diffraction patterns of Ni-P electrodeposited films with various P contents gradually changed from sharp peaks to broad peaks with increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The composition and properties of the Ni-P bulk prepared by electrodeposition from the same watts bath were presented in order to compare with those of nanowires and nanotubes. It was found that the relationship between the P content and current density applied for the electrodeposited Ni-P bulk alloy is almost similar to those of nanowires and nanotubes above [17]. Those outcomes indicated that electrodeposition of the P source used in the bath is conducted more preferentially in the low cathodic-current-density region to provide the high P composition ratio.…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…The composition and properties of the Ni-P bulk prepared by electrodeposition from the same watts bath were presented in order to compare with those of nanowires and nanotubes. It was found that the relationship between the P content and current density applied for the electrodeposited Ni-P bulk alloy is almost similar to those of nanowires and nanotubes above [17]. Those outcomes indicated that electrodeposition of the P source used in the bath is conducted more preferentially in the low cathodic-current-density region to provide the high P composition ratio.…”
Section: Resultssupporting
confidence: 50%
“…At high P contents had no magnetic properties [17]. The obtained Ni-P nanotube and nanowire arrays with various P contents showed the same magnetic properties as the alloy films.…”
Section: Characterization Of the Magnetic Properties For The Ni-p Alloymentioning
confidence: 82%
See 2 more Smart Citations
“…21) Furthermore, with regard to the P composition range for forming amorphous in the deposited films, Masumoto et al concluded that the P composition range for forming the amorphous phase should surround the P composition of eutectic point since around this composition, the deposited films can be quenched most readily with the lowest energy. 22) However, many experimental results [23][24][25][26] obtained by our laboratory including the result of the present study, have proved that the P composition range for forming the amorphous phase should surround the composition range for forming the intermetallic compound.…”
Section: Amorphous Phase Formation In the Deposited Filmsmentioning
confidence: 85%